ANALISIS MANAJEMEN RISIKO WAKTU DAN KEMAJUAN PADA PROYEK KONSTRUKSI PEMASANGAN BAJA PEB VIETNAM (PRE-ENGINEREERED BUILDING) GUDANG PT GOLDEN INOVASI INDONESIA DI KAWASAN INDUSTRI KENDAL - Rahman, Dedy Nur Rahman; Santosa, F. Rooslan Edy; Lesmana, Diyan (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2026)
Construction projects using the Pre-Engineered Building (PEB) system have a high dependency on prefabrication processes and international supply chains, making them vulnerable to uncertainties in project duration and work progress. Previous studies indicate that delays in PEB projects are commonly caused by logistical risks, overseas fabrication delays, and external factors such as weather conditions. However, deterministic scheduling approaches that are still widely applied are considered insufficient to comprehensively represent project duration uncertainty. This study aims to identify and analyze time-related risks affecting the progress of a construction project involving the installation of Vietnam-imported PEB steel structures at the warehouse of PT Golden Inovasi Indonesia in the Kendal Industrial Area. In addition, this study seeks to determine dominant risks, analyze the project’s critical path, and evaluate the effectiveness of mitigation and acceleration strategies in reducing project duration. A quantitative research approach was employed using both primary and secondary data. Risk identification and assessment were conducted through expert judgment using the Analytical Hierarchy Process (AHP) and Failure Mode and Effect Analysis (FMEA). Project scheduling analysis was performed using the Critical Path Method (CPM), while duration uncertainty was analyzed using Monte Carlo simulation to obtain probabilistic project duration estimates. The results indicate that the initial project duration based on CPM was 147 days, with the critical path occurring in the stages of design finalization, PEB steel fabrication in Vietnam, international delivery, and erection works. Dominant risks included delays in steel fabrication and material delivery, schedule discrepancies with site conditions, and extreme weather. The implementation of mitigation and acceleration strategies on critical activities reduced the project duration to 120 days, representing a time reduction of 27 days (18.37%). Monte Carlo simulation results demonstrate an increased level of project completion reliability after mitigation measures were applied